Creating Effective Online Collaborative Educators - Prendergast, Gerard A. (Proceedings of the International Conference on Networked Learning, 2000)
The early pioneers in online education tried to recreate the world that they were familiar with, the face-to-face classroom or lecture theatre, in cyberspace. There is now a recognition that this approach, to some extent, is limiting. We are starting to recognise that we need to change the way we think and operate, if we are to reap the benefits of Computer Mediated Communication as an educational tool. When the movie camera was first invented, the early filmmakers filmed plays. It took a few years for them to learn how to exploit the power of the movie camera. If you look at how a film is made today and compare it with the production of a play, you will find that there are some significant differences. Some of the core features in the production of plays and films remain the same. The movie camera permits a great many additional techniques to be exploited. This has resulted, over time, in a whole new way of operating, in order to exploit the medium fully. With the medium of Computer Mediated Communication (CMC) we are still developing educational techniques that will reap the learning benefits that the medium may offer.